2015
DOI: 10.1007/s00380-015-0675-z
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal thoracic artery grafting in octogenarians: where are the benefits?

Abstract: The use of bilateral internal thoracic artery (BITA) grafting for myocardial revascularization is usually discouraged in the very elderly because of increased risk of perioperative complications. The aim of the study was to analyze early and late outcomes of BITA grafting in octogenarians. From January 1999 throughout February 2014, 236 consecutive octogenarians with multivessel coronary artery disease underwent primary isolated coronary bypass surgery at the authors' institution. Six of these patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
0
31
3
Order By: Relevance
“…The exceptions have been the rare cases where one or both ITAs were unsuitable as coronary grafts, when there was an unexpected operative finding of severe cardiac dysfunction, or when a rapid ischemic worsening of hemodynamics needed immediate institution of cardiopulmonary bypass. Thus, the rate of use of both ITAs was very high (65 %) even in the patients with LV dysfunction of the present study [20][21][22]. Furthermore, in this study, the use of both ITAs resulted to be an independent protective factor for hospital death.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The exceptions have been the rare cases where one or both ITAs were unsuitable as coronary grafts, when there was an unexpected operative finding of severe cardiac dysfunction, or when a rapid ischemic worsening of hemodynamics needed immediate institution of cardiopulmonary bypass. Thus, the rate of use of both ITAs was very high (65 %) even in the patients with LV dysfunction of the present study [20][21][22]. Furthermore, in this study, the use of both ITAs resulted to be an independent protective factor for hospital death.…”
Section: Discussioncontrasting
confidence: 49%
“…This was not an entirely unexpected result. Although many published series [21,[24][25][26][27][28] and a randomized controlled trial as well [29] have shown no significant differences in the early mortality between bilateral and single ITA grafting, in many out of these studies, however, hospital (or 30-day) mortality was lower (albeit not significantly) in bilateral than in single ITA grafting. Moreover, almost none of these studies discriminate between patients with and without LV dysfunction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, improvements in technical management, particularly the development of innovative extracorporeal circulatory systems, the use of off-pump CABG and the increased use of pedicled arterial conduits have been proven effective in improving outcomes, although they have not completely eliminated the morbidity in this high-risk population. [8][9][10][11][12][13][14] Although improved long-term outcomes obtained with the use of arterial grafts for coronary revascularization in comparison with the traditional association of a single arterial and saphenous vein grafts have been demonstrated in the overall population, 15) the efficacy of this newer technique in the elderly remains difficult to verify because their shorter life expectancy due to advanced heart disease, associated with severe comorbidities. [16][17][18][19][20][21] Moreover more widespread use of this technique is limited by concerns on the potential morbidity, particularly the longer time required to perform the operation and the possibility of deep sternal wound infection in case of bilateral internal thoracic artery harvesting due to the deFrom the…”
Section: -6)mentioning
confidence: 99%
“…Gatti, et al 10) reported the results of a retrospective no-propensity matched study designed to investigate potential differences in terms of early mortality and perioperative complications after BITA grafting in octogenarians in comparison with standard revascularization.…”
Section: Bilateral Internal Thoracic Artery Revascularization In the mentioning
confidence: 99%